Building Leadership Capacity in Elementary Students through Interactive Game-Based Learning in the Kampus Mengajar Program - Hamidaturrohmah, Hamidaturrohmah; Muzakki, Muhammad Alie; Putri, Aprilia Riyana; Niswah, Nihlatun (Journal of Leadership in Organizations, 2025)
Introduction/ Main Objectives: Today's complex global challenges demand that young people develop robust leadership skills, critical thinking abilities, and respectful conduct to address emerging issues effectively. This study aimed to explore the implementation of Interactive game-based learning in building the leadership capacity of students in elementary schools. Background problem: This research is conducted in response to the deficiency in character values and inadequate literacy and numeracy skills among elementary school students. Novelty: This research study elaborates in-depth on the leadership character values that can be applied to elementary school students through game-based learning. Research Method: This research uses a descriptive qualitative method in the form of a case study with a participant observation approach. The study was conducted in 5 elementary schools that are partner schools of the Kampus Mengajar Program in Jepara Regency. Findings/Result: This research shows that the implementation of interactive game-based learning in building students' leadership skills is carried out through four innovative game activities. First, the Harkasi Game (literacy treasure) stimulates leadership values of responsibility and cooperation. Second, the Hitari Game promotes leadership values of self-confidence and critical thinking. Third, the Siberta Game educates leadership values such as creative thinking and empathy. Fourth, the Ultrasi Game stimulates leadership values of honesty and creative thinking. Conclusion: Overall, the interactive game-based learning implemented in the partner elementary schools of the Kampus Mengajar Program has a positive impact on students, with 83% of 53 students showing improved leadership skills. Thus, it can be a solution to build leadership abilities.